Statistical Analysis and Impact of Tourism Industry on Economic Growth of Nepal - Acharya, Bhumi Raj; Adhikari, Madhusudan (Nepalese Journal of Management and Technology, 2025)
This study examines the impact of the tourism industry on economic growth in Nepal, with particular emphasis on whether growth is driven by tourist volume or by value-generating tourism activities. A descriptive and analytical research design was employed using secondary time-series data covering fiscal years 2015/16 to 2024/25, sourced from the Nepal Tourism Board and Nepal Rastra Bank. The study applied descriptive statistics, Pearson correlation, and multiple regression analyses to evaluate the relationship between key tourism indicators, tourist arrivals, average length of stay, tourism royalties, tourism-related employment, and foreign exchange earnings, and economic growth measured by tourism’s contribution to GDP. The findings reveal that foreign exchange earnings from tourism exert a positive and statistically significant influence on economic growth. In contrast, tourism employment shows a significant but negative relationship, reflecting challenges related to low labor productivity and seasonality. Tourist arrivals, length of stay, and tourism royalties exhibit statistically insignificant effects on economic growth. The results underscore the importance of prioritizing high-value, revenue-intensive, and sustainable tourism strategies to enhance Nepal’s long-term economic growth.